When and Why Is Research without Consent Permissible?. Issue 2 (19th February 2016) - Gelinas, Luke; Wertheimer, Alan; Miller, Franklin G.
Abstract: The view that research with competent adults requires valid consent to be ethical perhaps finds its clearest expression in the Nuremberg Code, whose famous first principle asserts that "the voluntary consent of the human subject is absolutely essential." In a similar vein, the United Nations International Covenant on Civil and Political Rights states that "no one shall be subjected without his free consent to medical or scientific experimentation." Yet although some formulations of the consent principle allow no exceptions, others hold that informed consent is not always strictly necessary for ethical research. The U.S. federal regulations known as the "Common Rule, " which govern research with human subjects, lists several conditions for waiving consent. However, neither guidance documents on the ethics of clinical research nor the literature in bioethics contains a general justification of research without consent. The purpose of this paper is to advance a justificatory framework that will explain why research without consent is permissible in paradigmatic cases and that can be useful in analyzing cases about which there is (or is likely to be) disagreement. We argue that research without consent can be justified on two grounds: if it stands to infringe no right of the participants and obtaining consent is impracticable, or if the gravity of the rights infringement is minor and outweighed by the expected social value of the research and obtaining consent is impracticable.